As dimensões do trabalho profissional do assistente social mediadas na perícia social e duas determinações no capitalismo - Hamburgo, Joana de (2022)
This dissertation aimed to analyze the dimensions of professional work mediated in the social expertise carried out by social workers inserted in the Court of Law of Rio Grande do Sul, aiming to contribute to the theoretical-practical improvement of the theme by the Social Work. The theoretical categories were work, Court of Law, theoretical-methodological dimension, ethical-political dimension, technical-operative dimension and social expertise. A conceptual appropriation of State and Law was sought to contextualize the locus of study. The foundation was given in the dialectical and historical materialist method and in the categories contradiction, historicity, mediation and totality. The research problem that guided the work was: how are the dimensions of the professional work of the social worker mediated in the social expertise carried out at the Court of Law of Rio Grande do Sul? The quantitative-qualitative research used triangulation with the application of a questionnaire to social workers at the Court of Law of Rio Grande do Sul; document analysis in social reports; professional experience; document analysis in resolutions of the Federal Council of Social Work and national laws relevant to social expertise; and literature review. The data analysis procedure was based on content analysis for qualitative data and statistical treatment for quantitative data. The results indicated good working conditions about material resources and wage, however, exploitation in time and intensity of work. Professional practice takes place in the immediacy of the response to institutional demand, with fragility in the mediation of theory and method in Marx and in a fine line between observance and non-observance of professional secrecy, by including in the social report the facts narrated by users in the interviews. Finally, despite the mastery in the use of instruments and techniques, the lack of parameters on the concept, nomenclature and structure of the report and social opinion is evident.